Simultaneous ipsilateral hip and knee dislocation: Management and outcome – A case report - Christian G. Falgons; Stephen J. Warner (Trauma Case Reports)
Case: This clinical case report presents a 40-year-old male who sustained an ipsilateral hip and knee dislocation with ipsilateral femoral head fracture and incomplete femoral neck fracture following a motorcycle collision. Conclusion: This report describes acute and later definitive orthopedic care and management, with focus on urgent interventions and timing of immediate treatments. Given the presented patient's favorable clinical outcomes, return to baseline activities, and absence of significant sequelae following injury, the considerations from the acute management and surgical planning of this patient's injuries can be used as a reference for treating the rare injury of ipsilateral knee and hip dislocations.